DETERMINAN KUALITAS IMPLEMENTASI CORPORATE GOVERNANCE PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2004-2008 - Abdullah Taman; Bily Agung Nugroho (Universitas Negeri Yogyakarta, 2011)
Objective of this paper is to analyze determinant of implementation quality ofcorporate governance in companies listing in Indonesian Stock Exchange during period 2004-2008.Population in this study is entire listed companies in Indonesia Capital Market amountto 389 companies. Purposive samping is used to determine sample usage. The samples arefifty companies but one company is relaxed because of outlier. Analysis method used in thisstudy is multiple regression.This study concludes that determinants of implementation quality of corporategovernance are ownership concentration, investment opportunity set, and leverage.Simultaneously, they affect significantly to implementation quality of corporate governancewith F-value is 3.301 (sig. 0.029). Meanwhile, individually variable leverage affectssignificantly to implementation quality of corporate governance with t-value is 2.694 (sig.0.016).Key words: corporate governance, ownership concentration, investment opportunity set,leverage.